2015
DOI: 10.9734/bjast/2015/18148
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Urbanization in Nigeria

Abstract: This review revealed that there are several evidences of environmental impact of urbanization in Nigeria. The linkages between urbanization process and the environment are profound that the major components of the environment-air, water and land are adversely affected by the daily anthropogenic activities of urban residence and in the process of exploiting the natural resource base. The goal of ensuring environmental sustainability is greatly threatened by urbanization, which has created several serious enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Studies have argued that urbanisation has accelerated the economic and social development of cities, globally turning them into engines of economic growth and centres of innovation, while influencing their surrounding hinterlands (De Sherbinin et al 2007, Seto et al 2011, Cui, Shi 2012, Ohwo, Abotutu 2015. However, urbanisation has had wide-ranging impacts on the environment, from the local scale to the global (Kim, Baik 2005, Zhao et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have argued that urbanisation has accelerated the economic and social development of cities, globally turning them into engines of economic growth and centres of innovation, while influencing their surrounding hinterlands (De Sherbinin et al 2007, Seto et al 2011, Cui, Shi 2012, Ohwo, Abotutu 2015. However, urbanisation has had wide-ranging impacts on the environment, from the local scale to the global (Kim, Baik 2005, Zhao et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Using China as a case study, Li and Ma (2014) suggest that the turning point towards improved environment in the inverted U shape is about 60 percent rate of urbanization and that the inverted U-shaped association between urbanization/ economic growth and the quality of the environment is worldwide. Ohwo and Abotutu (2015) in their study revealed the evidences of environmental influence of urbanization in Nigeria. The associations between urbanization progression and the environment are indicated that the main mechanisms of the environment that include air, water and land are unfavorably distressed by the everyday anthropogenic actions of urban dwelling and in the course of exploiting the natural resource.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The second section of the literature review focus on the connection between urbanization and environmental pollution and the ones reviewed include Ohwo and Abotutu (2015) in their study revealed the evidences of environmental influence of urbanization in Nigeria. The associations between urbanization progression and the environment are indicated that the main mechanisms of the environment that include air, water and land are unfavorably distressed by the everyday anthropogenic actions of urban dwelling and in the course of exploiting the natural resource.…”
Section: Literature Reviewmentioning
confidence: 99%